Why and when to manage parking ? key indicators to be considered before implementing an on-street parking management system in Cape Town - Frydie, Imeraan (Department of Civil Engineering, 2024)
The City of Cape Town is responsible for the administration, management, and regulation of all public parking bays within the metropolitan area of Cape Town. On-street parking, within central business districts (CBD), aims to facilitate and provide access to short-term parking within short distances of places of business and opportunities, and the turnover of these parking bays is essential for the economic viability of these businesses. Historically, the implementation of newly managed parking areas was based on public outcry rather than proper planning. The purpose of this study is to understand why parking is managed, by looking at literature from around the world, then to see when management gets implemented. This study then wishes to develop a set of indicators that municipalities should consider monitoring before formal parking management gets implemented within Cape Town areas. The aim of this study was therefore to develop a list of indicators that needs to be surveyed on an ongoing basis to use parking efficiently as a travel demand management tool in Transport Planning, by knowing why and when to implement parking management, instead as an operational tool to facilitate management once the situation on-street becomes a problem. The methodology used in this study was to look at the historical literature from various parts of the world and determine what the main reasons for management parking are. Once it has been determined why parking is managed, the study aims to understand when to manage parking. Essentially develop a list of indicators, then set targets for these indicators, then when these targets have been achieved, the municipality can identify when to manage parking. Three areas were selected that could serve as a proxy for the Cape Town context and test these areas against the indicators. A residential area, Durbanville, was selected which, over the past few years, has seen land use changes driving up the competition and demand for onstreet parking. The second area selected was Camps Bay which is a recreational area with mixed-use and mixed demand for parking. The third area that was selected was De Waterkant which is a developed area with minimum off-street parking. The area is adjacent to the Cape Town CBD and therefore is subject to urban sprawl. Many drivers aim to park their vehicles for free all day and walk into the CBD. There is therefore massive competition for parking by residents, workers, and recreational parkers wanting to visit the local shops. It was found that the main reason for managing parking is to increase the viability of public transport, for parking bay turnover to increase business viability, and to reduce traffic congestion and CO2 emissions. Although part of the world has implemented parking 5 | Page management to increase revenue, the efficient use of parking is more linked to ensuring sustainability across the area locally and metro-wide, and therefore the revenue should be a result of proper and effective management rather than the main aim. There were 7 indicators established through this study which were tested against the 3 areas. When the surveyed areas were tested through the indicators, the outcomes were that parking management implementation was required in De Waterkant and Camps Bay. The Management in Durbanville was not recommended as certain triggers were not met. Regular monitoring allows for improved problem-solving from the municipality when demand outweighs supply. These indicators will vary between areas and may not be applicable in certain areas. Additionally, the development of the thresholds of these indicators also varies, however, this may inform part of a further study.